DUMPİNG SENDROMU(DS) VE BİRLİKTE OLAN ALKALEN REFLÜ GASTRİT SENDROMU (ARGS) İÇİN DÜZELTİCİ AMELİYATLAR - ERSAN, Yılmaz; ERGÜNEY, Sabri; DİRİCAN, Ahmet; ERTÜRK, Süphan; ÇİÇEK, Yusuf; KUŞASLAN, Ramazan (Cerrahpaşa Medical Journal, 2019)
Background and Design.- Many different remedial operation for dumping syndrome and associated alkaline reflux gastritis have been considered. No controlled trials have compared the relative efficiency of these operations. Analysis of their efficiency is difficult, because while many of the procedures have good early results, there are long term failures due to complications. Materials and Methods.- Clinical features and results of remedial operations of 21 patients with dumping syndrome and associated alkaline reflux gastritis syndrome treated between 1989 to 2001 were reviewed retrospectively. Preoperatively all patients who had symptoms were evaluated by upper gastrointestinal series, endoscopy and radionuclide scanning. Long term clinical follow-up data for all patients was collected by reviewing medical records, interviewing patients directly or through telephone call or both. Visick scale was used for clinical assessment. Results.- Among 21 patients,19 could be followed. Roux-en-Y gastrojejunostomy was succcesful in 10 patients, who had Visick-I and Visick-II scale. Roux stasis syndrome was developed in 1 patient. Near-total gastrectomy was performed in 1 patient due to stasis syndrome. Conclusions.- For patients with medically unresponsive, severe dumping and dumping/alkaline reflux gastritis symptoms, we recommend the following strategy: a) For patients with pyloroplasty, pyloric reconstruction should be the initial remedial operation, b) For patients with truncal vagotomy plus gastrojejunostomy, gastrojejunostomy should be taken down in initial remedial approach. c) For patients with prior Billroth-I or Billroth-II gastrectomy, Roux-en-Y conversion is the most effective corrective operation, although it has its own problems including Roux stasis syndrome.